Enhancing the thermoelectric figure of merit in engineered graphene nanoribbons - Sadeghi, Hatef; Sangtarash, Sara; Lambert, Colin J. (Beilstein Journal of Nanotechnology, 2015)
We demonstrate that thermoelectric properties of graphene nanoribbons can be dramatically improved by introducing nanopores. In monolayer graphene, this increases the electronic thermoelectric figure of merit ZTe from 0.01 to 0.5. The largest values of ZTe are found when a nanopore is introduced into bilayer graphene, such that the current flows from one layer to the other via the inner surface of the pore, for which values as high as ZTe = 2.45 are obtained. All thermoelectric properties can be further enhanced by tuning the Fermi energy of the leads.
Keywords: graphene nanoribbons; quantum transport; thermal conductance; thermoelectric figure of merit; thermopower